Entrepreneurship and its Determinants in Nigeria: Empirical Evidence from Micro and Small Enterprises in Kano State - Abubakar, S. Garba; Shazali, Abu Mansor; Fariastuti, Djafar (Publishing India Group, 2013)
The objective of this paper is to examine the determinants of entrepreneurship in Kano state. Survey research design was employed to collect data from the selected samples of micro and small entrepreneurs in the state. Questionnaire and interview instruments were used to collect data accordingly. Interview was purposely conducted to complement information obtained through the use of questionnaire by exploring to get more information directly from the selected key informants. Simple linear regression was used to estimate the coeffiients of all the variables in the regression model. In spite of high poverty and unemployment in the state, it is discovered that there is no motivation for poor and unemployed people to start up their own business. Therefore, lack of start up capital is found to be a major factor or determinant for entrepreneurship activity. Women were less likely to partake in entrepreneurial activities in comparison to their men counterpart. There is need for the government to revisit the existing microfiance policy so as to address the fiancial problem of the poor and unemployed. Women should be encouraged to participate in entrepreneurship through training and financial support.